Onnanoscale phenomena inthe electroacoustic sputtering process - W. H. Al-Tibbi; V. S. Minakov (Advanced Engineering Research, 2018)
Introduction. The effect of variable parameters of the electroacoustic sputtering (ELAS) process on the characteristics of the crystalline structure of hardening coatings is studied. The ELAS parameter values providing nanostructured cover coatings for machine parts and cutting tools are determined. Hardening through using such coatings allows achieving a significant (5-10 times) increase in the life of hardenable machine parts and various tools designed for mechanical processing. To obtain coatings with the desired properties of the surface layer, nanocrystalline materials should be selected. In this case, a certain content of the amorphous phase is permissible.Materials and Methods. To carry out the X-ray structural analysis, the X-ray diffraction Russian-made device DRON-3M was used. The Scherrer-Wilson method was applied to determine the granularity of particle blocks from the value of the intrinsic broadening of the diffractogram peaks. The conclusions obtained in this paper are based on the method of separation of the affecting factor contributions into broadening the diffraction reflection peaks (the Warren-Averbach method).Research Results. Depending on the process conditions and the technique for obtaining nanostructured materials, a nonuniquely interpretable change in the indices of the diffraction peaks broadening occurs, which is generally characteristic of nanocrystalline metals. One of the possible explanations for this phenomenon is the presence of a nanosized effect in the hardened layer. The occurrence of the nanocrystalline structure in the sputtered layer verifies the calculated values of the dimensions of the coherent scattering regions (CSR). The occurrence of affecting values of the misorientation angle of the crystal structure is verified by the CSR value for the investigated 110 and 220 reflexes, which is supported by a high percentage of the amorphous phase.Discussion and Conclusions. The electroacoustic scattering method is promising for obtaining nanocrystalline structures in the surface and subsurface layers of the sprayed samples. The ELAS process variables variation leads to the parameter spread of the crystal lattice and coherent scattering areas. In this case, there is no definite trend. In the future it is expected to solve the given problem. First, experiments will be conducted to determine the optimal sputtering regimes that could stimulate the formation of nanocrystalline structures. Secondly, visual observation and evaluation of the sprayed layer structure using electron microscopy is planned.